KOMUNIKASI LINGKUNGAN: UPAYA MEWUJUDKAN ARBORETUM GAMBUT SEBAGAI EKOWISATA DI KABUPATEN BENGKALIS - Anissa Febriani Primananda; Fatmawati Moekahar (IAI Darussalam, 2020)
The Peat Arboretum is one of the PT. Pertamina RU II, Sungai Pakning which is managed by the Kampung Jawa community group. This research was motivated by the discovery of land that was saved from peatland fires around Kampung Jawa in the 2013-2015. Basically, the people of Kampung Jawa are people with low education and lack of public awareness of environmental sustainability as an edutourism area. Therefore, this research aims at how PT. Pertamina RU II Sungai Pakning through its CSR activities communicated in building community participation to realize the Marsawa Peat Arboretum as ecotourism in Bengkalis Regency. In this study using qualitative research methods with a descriptive approach. research subjects were determined based on purposive sampling technique. Data collection techniques were carried out through in-depth interviews, observation, and documentation. The results of this study indicate that the environmental communication carried out by PT Pertamina in the CSR program in realizing the Peat Arboretum as ecotourism is carried out through several stages, namely assessment, planning, production and action and reflection. Of the four, community participation in realizing the Peat Arboretum as ecotourism in Bengkalis Regency has been effective, this can be seen from the voluntary community involvement in programs that lead to social change. The four stages are educational, solution and comprehensive efforts in realizing the Peat Arboretrum as Ecotourism in Bengkalis Regency.